2018
DOI: 10.1016/j.jval.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Sustained 3-Year Benefits in Quality of Life After Percutaneous Coronary Interventions in the Elderly: A Prospective Cohort Study

Abstract: Elderly patients experienced sustained long-term improvement in quality of life comparable with younger patients after PCI. Our findings suggest that age per se should not deter against revascularization because of sustained benefit in HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
4
10
1
Order By: Relevance
“…Conversely, Veenstra et al [50] found higher physical dimension scores among younger adults after invasive coronary procedures. Similarly, Yan et al [61] also found a significant gain in two dimensions of QoL (pain and depression) for younger patients at 36 months after treatment. Azmi et al [51] found higher QoL score in patients on STEMI compared to those on NSTEMI/UA (p = 0.045).…”
Section: Changes In Qol Among Acs Patients After Treatmentmentioning
confidence: 75%
See 2 more Smart Citations
“…Conversely, Veenstra et al [50] found higher physical dimension scores among younger adults after invasive coronary procedures. Similarly, Yan et al [61] also found a significant gain in two dimensions of QoL (pain and depression) for younger patients at 36 months after treatment. Azmi et al [51] found higher QoL score in patients on STEMI compared to those on NSTEMI/UA (p = 0.045).…”
Section: Changes In Qol Among Acs Patients After Treatmentmentioning
confidence: 75%
“…Upon further critical appraisal through peer review, seven articles which assessed the secondary outcome were excluded as (i) the outcome of interest was not measured before and/or after treatment (5), (ii) outcome compared between ACS and non-ACS (1), and (iii) ACS patients who also had chronic kidney disease (1). Finally, 29 studies were included for review of which 16 studies [15,28,29,33,[39][40][41][42][43][44][45][46][47][48][49][50] assessed disease specific QoL and 13 studies [26,[51][52][53][54][55][56][57][58][59][60][61][62] assessed generic QoL. Of these studies, 13 studies were RCTs, 12 were cohort studies, two were cross-sectional studies, and two were reviews.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wijeysundera et al (2014) found that patients who got revascularization (PCI/CABG intervention) had more improvement in the EQ-5D score index compared to the control group after 12 months. Yan et al (2018) also found that PCI intervention was still able to give improvement after 36 months. A similar result was also reported by Baron et al (2017) that the EQ-5D index score of CHD patients who got PCI/CABG intervention had improved after measurements (at one month, 24 months, and 36 months).…”
Section: Pci/cabg Interventionmentioning
confidence: 87%
“…Additionally, an improvement in EQ-5D score index and EQ-VAS score after measurement at 12 months was found by Zajac et al (2016) in CHD patients who previously got CABG and then got PCI intervention. HR-QOL improved after PCI/CABG intervention because it directly alleviates the symptoms (angina) experienced by patients (Wijeysundera et al 2014;Zajac et al 2016;Baron et al 2017;Yan et al 2018).…”
Section: Pci/cabg Interventionmentioning
confidence: 99%